Pengkajian tentang Hujan menurut Perspektif Hadits - Annisaa Siti Zuadah; Cessi Oktavianti; Indah Fahira Ainun Nisa (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the hadith about rain through content analysis and library research, using qualitative research methods. The discussion of this research includes the hadiths about rain. This study concludes that rain is a complex cycle, where rain has a meaning as something unseen, a gift (grace) or a calamity (punishment) depending on the point of view of everyone who sees it. In the Qur'an and hadith it is said that rain (water) is the source of life. Water is the main component that motivates people to settle down and naturally drives the growth of civilization. The rain cycle existed long before modern biology, where it was found in the texts of the Al-Qur'an and hadith from long before.